THE INFLUENCE ADMINISTRATION OF UREA AND NASA LIQUID ORGANIC FERTILIZER ON GROWTH AND PRODUCTION OF PAKCOY MUSTARD PLANT (Brassica rapa L.) - ronald indra wahyudhi; Agus Sugianto; Sugiarto sugiarto (AGRONISMA, 2022)
This study aims to determine the effect of the combination of UREA and NASA liquid organic fertilizer on growth and production of pakcoy mustard plant (brassicarapa l.) This research was conducted in Bululawang Subdistrict, Malang Regency and integrated laboratory of Islamic University of Malang with an altitude of Â± 460 masl, an average temperature of 22ÂºC. Rainfall was 675 mm. This research was conducted from Juni 2020 to Juli 2020. The method used in this study used a randomized block design (RBD) which was arranged in a factorial manner. Factor 1 is fertilizer: UREA and factor 2 is NASA liquid organic fertilizer. The details of the treatment of the first factor are S0 : a control not treated; S1 : 300 kg urea/ha and S2 : 350 kg urea/ha. The second factor is the provision of NASA Poc fertilizer. The treatments were V0 : Control (no treatment) V1 : 1.5 ml/L NASA Poc fertilizer and V2 : 2.5 ml/L NASA Poc fertilizer. The treatment combinations of the two factors are presented in Table 1. In total from the treatment combinations there were 9 combinations, each treatment was repeated 3 times with 3 plants sampling plants. Based on the results of statistical analysis of growth showed that in general the treatment of Urea 350 kg/Ha and administration of 2.5 ml/L POC NASA gave a significant effect on plant height, number of leaves, and leaf area. However, the higher the dose of Urea 350 kg/ha, can reduce the concentration of NASA POC 1.5 ml/L.